The contemporary world - Sanchez, Joje Mar P.; Sumalinog, Gino G.; Argate, Rex T.; Cadosales, Maria Nancy Q. (Quezon City : Lorimar Publishing Inc., 2024)
"The contemporary world is characterized by dynamic and complex systems that are interdependent and constantly evolving. In this book, we explore the key issues and trends shaping our world today, including globalization, economic globalization, socio-cultural systems, economic systems, sustainable development, and global citizenship. Each unit in this book is designed to provide a comprehensive and an in-depth analysis of a specific aspect of the contemporary world and is accompanied by a set of learning outcomes, activities, assessments and unit projects."
Includes references.
English.
Keywords: Globalization